Interaction between Language Testing Research and Classroom Testing Practice - Ali Mansouri Nejad; Farhad Pakdel; Ali Akbar Khansir (ÜNİVERSİTEPARK Limited, 2019)
The existing gap between research and practice in language testing has posed a huge challenge to language teachers. In particular, this study intended to examine language testing research and classroom testing activities for their degree of interaction from Iranian EFL teachers' points of view. The analysis drew on the questionnaire developed by Nassaji (2012), which consists of quantitative and qualitative sections. The data were collected from 200 language institute teachers in Bushehr, Iran. The findings indicated that most of the teachers confirmed their familiarity with language testing research, while only a few believed that they were able to conduct or publish testing research. Although the participants acknowledged that the information gained from reading language testing could be valuable for their testing performances, they found their experience more relevant than knowledge gained from language testing research. This study also illustrated that there is a growing consensus among teachers in that there should be collaboration between researchers and teachers in testing practices.